Plant eating behavior in domestic cats: Support for the hair evacuation hypothesis - Bensel, Kara N.; Rudock Bowman, Megan E.; Hughes, Nicole M. (Journal of veterinary behavior, 2025)
Dogs and cats have been widely observed eating grasses and other plants, and then regurgitating this matter, undigested, shortly thereafter. Previous researchers have hypothesized that consumption of fibrous leaves and stems by carnivores aids in the expulsion of parasites and/or hair trapped in their digestive tracts from feeding and grooming. Although direct interactions between ingested leaves and parasites have been reported in stools of many mammalian species, no such interactions have been reported for hairs expelled orally or in stools. In this study, we used scanning electron microscopy (SEM) to examine six regurgitated plant masses produced by two indoor/outdoor domestic cats belonging to one of the authors. DNA barcoding was additionally used to identify plants in all samples. SEM revealed that all consumed/regurgitated plant matter exhibited microscopic serrations and/or epidermal hairs, which were similar in size to cellulose fibers added to pet food to mitigate hairballs (50–500 µm). Furthermore, direct interactions between these microstructures and animal hairs were clearly visible in all regurgitated samples examined. Ingested plant material included grasses as well as several other indoor and outdoor plant species, representing a variety of taxonomic groups. These findings are consistent with the hypothesis that consuming textured leaves is a healthy behavior that could help cats and other carnivores avoid intestinal blockages caused by hairs ingested during feeding or grooming. [Display omitted]